Early cinema in Scotland - Caughie, John (Edinburgh : Edinburgh University Press Ltd, 2018)
Focusing on the social experience of cinema and cinema-going, this collection of essays provides a detailed context for the history of early cinema in Scotland, from its inception in 1896 until the arrival of sound in the early 1930s.
CHAPTER 10 The Talkies Triumphant: Scottish Cinema and the Coming of SoundCHAPTER 11 Filmography of Scottish-themed Fiction Films; Bibliography; Index.
Includes bibliographical references (pages 239-249), filmography (pages 188-238) and index.
Print version record.
JSTOR
Keywords: Motion pictures -- Social aspects -- Scotland -- History -- 20th century; Motion pictures -- Scotland -- History -- 20th century; Cinéma -- Aspect social -- Écosse -- Histoire -- 20e siècle.; Cinéma -- Écosse -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference; PERFORMING ARTS -- Film & Video -- General; Motion pictures -- Social aspects; Motion pictures; Scotland; 1900-1999; Electronic books; History